Cross-immunity between respiratory coronaviruses may limit COVID-19 fatalities (2020)
Of the seven coronaviruses associated with disease in humans, SARS-CoV, MERS-CoV and SARS-CoV-2 cause considerable mortality but also share significant sequence homology, and potentially antigenic epitopes capable of inducing an immune response. The degree of similarity is such that perhaps prior exposure to one virus could confer partial immunity to another. Indeed, data suggests a considerable amount of cross-reactivity and recognition by the hosts immune response between different coronavirus infections. While the ongoing COVID-19 outbreak rapidly overwhelmed medical facilities of particularly Europe and North America, accounting for 78% of global deaths, only 8% of deaths have occurred in Asia where the outbreak originated. Interestingly, Asia and the Middle East have previously experienced multiple rounds of coronavirus infections, perhaps suggesting buildup of acquired immunity to the causative SARS-CoV-2 that underlies COVID-19. This article hypothesizes that a causative factor underlying such low morbidity in these regions is perhaps (at least in part) due to acquired immunity from multiple rounds of coronavirus infections and discusses the mechanisms and recent evidence to support such assertions. Further investigations of such phenomenon would allow us to examine strategies to confer protective immunity, perhaps aiding vaccine development.